Bioethics in public university education in health sciences in Perú - Paredes Cohaila, Ana Alondra; Alca Gómez, Américo; Pezo Jiménez, Omar (Acta Bioethica, 2024)
The purpose of this research lies in evaluating the current state of higher university education about bioethics studies in the faculties of health sciences in the Peruvian territory. The methodological design adopts a descriptive level with a mixed approach that is divided into two stages: The first consists of a qualitative theoretical-analytical-rational analysis, followed by a subsequent empirical analysis with a quantitative, descriptive, and cross-sectional approach. The main discoveries refer to the existence of nineteen licensed public universities in Peru that offer the Human Medicine degree. However, it was found that the Bioethics course is only available in nine of these institutions. In summary, it can be affirmed that in the educational programs of careers related to health sciences, attempts are made to address ethical principles from different perspectives, for example, through courses on general ethics or deontology. However, this strategy is not considered adequate. In addition, it is imperative to promote an educational policy within the faculties of health sciences that mandates the mandatory inclusion of a bioethics course in the curricula of health sciences programs.